Penerapan Metode Bermain Peran (Role Playing) dalam Mengembangkan Kognitif Anak Usia 5-6 Tahun - Wardah Anggraini; Anggi Darma Putri (Program Studi Pendidikan Islam Anak Usia Dini, UIN Sunan Ampel Surabaya, 2019)
This study aims to find out how the application of the role playing method in developing cognitive skills of children aged 5-6 years. The problem in this study is the low cognitive development of children aged 5-6 years and the hope that the role playing method still uses limited media in RA Az-Zahra Natar, South Lampung. The method used in this research is a descriptive qualitative method that describes how the role playing method is used at RA Az-Zahra Natar, South Lampung. Data collection techniques used were observation, interviews and documentation. Analysis of the data used is the analysis of miles and huberman model data, namely data reduction, data collection and conclusion drawing. Based on data collection and analysis conducted there are several findings of research results about playing a role in developing cognitive children aged 5-6 years. The results of this research are the application of the steps used in role playing, i.eWarming up (warming up), participants (choosing players), setting the stage, observers (preparing observers), holding (ensuring roles), discussion and evaluation, reusing (playing back roles), second discussion and evaluation, various conclusions and experiences